On the CP Violation Phase in a Neutrino Mixing Model with an A4 Flavor Symmetry - Van, Phi Quang; Van, Nguyen Thi Hong (Communications in Physics, 2016)
Neutrino masses and mixing in an extended standard model acquiring an A4 flavour symmetry are considered. The corresponding three-neutrino mixing matrix obtained via a pertur- bative method allows us to determine the Dirac CP violation phase (δ_CP) as a function of the mixing angles (θ_12, θ_23, θ_13). Then, numerical values and distributions of δ_CP are given. The latter values are quite close to the global fits of the experimental data for both the normal ordering and inverse ordering of the neutrino masses.